Implementation of the Sustainable Quality Family Village Program in Bedagung and Tapen Villages, Magetan Regency - Suryati, Lisa; Hilman, Yusuf Adam; Triono, Bambang; Ridho, Irvan Nur (Jurnal Pallangga Praja (JPP), 2024)
Bedagung Village and Tapen Village are the implementers of the Quality Family Village (Kampung Keluarga Berkualitas) Program in Magetan Regency. These two villages are both classified as sustainable, but in their implementation, they have varying outputs. Therefore, this research is important to understand how the program is implemented in each village. This study aims to analyze the implementation of the Sustainable Quality Family Village Program in Bedagung Village and Tapen Village, Magetan Regency. This research uses a qualitative descriptive approach with data collection techniques including interviews, observation, and documentation. The technique for determining informants combines two methods: snowball and purposive sampling. This study employs Edward III's Public Policy Implementation Theory to analyze the data. The results show that the implementation of the Sustainable Quality Family Village Program in Bedagung Village and Tapen Village, Magetan Regency, has successfully improved the quality of life of their communities. The communication carried out aligns with the dimensions of clarity and consistency. Its implementation is also supported by trained human resources as well as adequate financial support and facilities. Additionally, there is a clear commitment among policy implementers and a new bureaucratic structure that facilitates the program's execution. Despite some challenges, such as a shortage of PLKB officers, the program has progressed with cross-sectoral support and active community participation.